Pengembangan Perangkat Pembelajaran Geografi Berbasis Masalah Pada Siswa Kelas XI SMA Negeri 6 Sigi - Abdul Hamid Salotan; Junarti (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2021)
This study aims to develop the problem-based learning which is valid, practical, and effective. The development of the learning model in this study using a model of the development of the 4-D app developed by Thiagarajan, Semmel & Semmel have been modified. The results showed that the learning device developed researchers can be said to be valid based on the table of criterion validity, with the value of 3.13, then said practically by looking at the practicality of the observation device problem-based learning 1.76 from the category of feasibility (of 1.5 ≤ M ≤ 2,0). Then said to be effective by looking at the level of the ability of teachers in managing to learn is 3.3 criteria (3.00 ≤ tkg 4.00). The activity of students in learning the average time that students meet the ideal time, students ' response to the student book and LKPD said to be very positive because it is included in the category of (3,5 ≤ RS < 4,0), and the level of achievement of the learning outcomes of students can be seen with the completion of all the students in the class, which amounts to 15 people, so the device problem-based learning on learning geography has met the criteria of valid, practical and effective, and feasible to be developed in the process of teaching and learning.